Manufacturing Process Development for Thin Film Filaments as a New Product - TUNABOYLU, BAHADIR (Springer Science and Business Media Deutschland GmbH, 2021)
Thin films of rare-earth hexaborides are promising for wear and corrosion protective, decorative, and thermionic coatings. Among many hexaborides available, due to its unique properties lanthanum hexaboride (LaB6) is used as a bright and long life thermionic electron source mostly in electron microscopes. Unlike single-crystal LaB6 cathodes used today, LaB6 thin-film coated metal filaments can be advantageous due to their simple design, easy installation, cost-efficient manufacturing, and less energy consumption. In the study, LaB6 thin films were grown onto tantalum, molybdenum, and tungsten wire-substrates using magnetron sputtering. Tape-test was used on the film surface to determine the adhesion of the LaB6 films to the substrates. The morphology, structure, and stoichiometry of tape-tested films were investigated by stereo microscopy, scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). Stereo microscopy and SEM analysis showed that the films were grown by magnetron sputtering have dense, fine columnar structure without peeling or flaking. In the XPS analysis of LaB6/W film it was observed that the film was oxidized and there were no peaks of any element other than lanthanum, boron, and oxygen found. The analysis shows that the composition of the film was LaBx coated over the tungsten (W) substrate at the deposition conditions. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Lanthanum hexaboride (LaB6) thin film filament; Magnetron sputtering (MS); Scanning electron microscope (SEM); Thermionic coatings; Transmission electron microscope (TEM)